The IceCube Neutrino Observatory Part V: Neutrino Oscillations and Supernova Searches - Collaboration I; Aartsen MG; Abbasi R; Abdou Y; Ackermann M; Adams J; Aguilar JA; Ahlers M; Altmann D; Auffenberg J; Bai X; Baker M; et al. (2018)
Papers on neutrino oscillation and supernova searches submitted to the 33nd International Cosmic Ray Conference (Rio de Janeiro 2013) by the IceCube Collaboration. With an array of 5160 photomultiplier tubes, IceCube monitors one cubic kilometer of deep Antarctic iceatthegeographicSouthPole.NeutrinosaredetectedviatheCherenkovphotonsemittedbychargedsecondaries from their interactions in matter. Due to low ice temperatures, the photomultipliers dark noise rates are particularly low. Therefore a collective rate enhancement introduced by interacting neutrinos in all photomultipliers can be used to search for the signal of galactic core collapse supernovae, even though each individual neutrino interaction is sub-threshold for forming a trigger. At present, rates of individual photomultipliers are recorded in 1.6384 ms intervals which limits the time resolution and does not allow to exploit signal correlations between the sensors. An extension to the standard data acquisition, called HitSpooling, overcomes these limitations by buffering the full raw data stream from the photomultipliers for a limited time. Thus, the full set of data can be analyzed when a supernova occurs, allowing for the determination of the average neutrino energy and the analysis of the ﬁne time structureoftheneutrinolightcurve.TheHitSpoolingsystemwillalsosigniﬁcantlyhelpinunderstandingthenoise behavior of the detector and reduce the background induced by atmospheric neutrinos to the supernova analysis.